If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5(x + -6) = 5(x + -5) Reorder the terms: 5x + 5(-6 + x) = 5(x + -5) 5x + (-6 * 5 + x * 5) = 5(x + -5) 5x + (-30 + 5x) = 5(x + -5) Reorder the terms: -30 + 5x + 5x = 5(x + -5) Combine like terms: 5x + 5x = 10x -30 + 10x = 5(x + -5) Reorder the terms: -30 + 10x = 5(-5 + x) -30 + 10x = (-5 * 5 + x * 5) -30 + 10x = (-25 + 5x) Solving -30 + 10x = -25 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -30 + 10x + -5x = -25 + 5x + -5x Combine like terms: 10x + -5x = 5x -30 + 5x = -25 + 5x + -5x Combine like terms: 5x + -5x = 0 -30 + 5x = -25 + 0 -30 + 5x = -25 Add '30' to each side of the equation. -30 + 30 + 5x = -25 + 30 Combine like terms: -30 + 30 = 0 0 + 5x = -25 + 30 5x = -25 + 30 Combine like terms: -25 + 30 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 6+3=36 | | 8x+8y=240 | | .33333x-21=33 | | 3x+12=2x+6 | | t*2+4t*2= | | 3h+28=82 | | 6+3=56 | | 4(2x)+4(3x)= | | 14+5x=(-x+3)-11 | | -13x+16=10 | | 2x-25+3x+x+6+4x-11=360 | | -4x-2(8x+1)=-2x-10 | | 4+3=56 | | 5(x+3)-5=2x+1 | | -2x-25+3x+x+6+4x-11=360 | | -2x^2-6x-9=0 | | 6-6=3x | | 12.7(x+11)=61.6 | | y+10.24=5.3 | | 3b-7=8 | | 4c-2c+3=17 | | 2p+6b=675 | | -2-25+3x+x+6+4x-11=360 | | 12+-14= | | -6(v+2)+4v+5=7v+12 | | -2x-59=21-7x | | 1+x-x^2-x^4=0 | | 9(r-8)= | | 2(3x-8)-4=10 | | 12x=126 | | -0.125(x+7)=20 | | 11+13=24 |